(untitled) (Innovation & Development in Engineering and Applied Science, 2026)
The provision of public transport stops is crucial for accessing quality services. However, in consolidated urban areas in countries classified as ’developing’, infrastructure is often inadequate, thus compromising accessibility and safety. The present project explores the perceptions of accessibility and safety among public transport users in the city of Quito. The approach is predicated on the analysis of the most salient indicators at bus stops, including ease of movement and access, the size of the stop, and indicators related to safety. This analysis is conducted through factorial exploration between indicators. The data will be collected through the administration of surveys, utilising immersive audiovisual equipment such as 360° videos and headphones. This equipment will be employed to present sixteen real-life bus stop scenarios to the participants. The study utilised a sample of 529 users, encompassing students and administrative personnel from the university. An exploratory factor model was developed in order to interpret the indicators that had been collected. The findings indicate a positive correlation between the indicators and the factors of accessibility and safety. Furthermore, the findings concerning transport indicators underscore the contextual influences exerted by users’ residential location. The survey methods employed in this study enabled the collection of data despite the perceptual complexity of the constructs under investigation. However, it is recommended that future research be expanded to include representative samples and incorporate additional latent variables to enhance the generalisability of the findings. The implementation of policy interventions necessitates a modular infrastructure capable of adapting to variations in urban density.